“Dimenticare” il bambino in auto. L’assenza che può uccidere. Introduzione - Masillo, Alice; Anzilotti, Carlo (Il sogno della farfalla, 2019)
The aim of this article is to introduce a series of papers dealing with the ever-increasing number of fatal episodes reporting children abandoned in the car. The phenomenon, well known as Forgotten Baby Syndrome, has been widely treated by the scientific international literature. According to the vast majority of researchers, the aetiology must be found in an interaction impairment in brain structures responsible for memory functioning. The papers published on this issue attempt to outline new research perspectives. On one hand they refuse to explain child abandonment in the car as a normal act of forgetfulness due to stress factors and to a daily hectic life. On the other, they identify in the annulment pulsion, theorised by Massimo Fagioli, the primary etiopathogenetic factor of this dramatic events. These are therefore recognized as manifestation of serious mental disorders.